Rezente Staatenbildung und Hauptstadt-Zentralität im Süd-Pazifik - Schöller, Peter (ERDKUNDE, 1978)
The southern Pacific Ocean is the only macro-region of the earth in which the decolonisation process is not yet complete. The most important question in this regard concerns the size and viability of newly created small island states. There is a tendency among economically well-situated islands or island groups to establish their own political-geo graphical identity and to separate themselves from economically weak regions, which are then scarcely able to continue to exist as independent states. The small island republic of Nauru, with its 7,000 inhabitants, is an extreme example of such wealthy micro-states. But larger states of the island realm are also faced with the problem of economic independence and territorial integration. This paper discusses the development of the capital to the point of being a leading functional centre, together with its role in the modernization and self-centralization of states in the case of Fiji, Tonga and Western Samoa. In this Apia, the primate town of Western Samoa, endowed with not-unfavourable pre-conditions presents the special problems of territorial concentration and carrying capacity. In future it will thus become increasingly important to establish higher central functions in supra-regional centres at supra-national levels. The obvious choice for a supra nationally effective central place of a higher order is Suva in Fiji, which has been the location of the University of the South Pacific since 1966